Multi-objective PSO based optimal placement of solar power DG in radial distribution system - Mahesh, K. (Engineering and Scientific Research Groups, 2017)
Ever increasing trend of electricity demand, fossil fuel depletion and environmental issues request the integration of renewable energy into the distribution system. The optimal planning of renewable distributed generation (DG) is much essential for ensuring maximum benefits. Hence, this paper proposes the optimal placement of probabilistic based solar power DG into the distribution system. The two objective functions such as power loss reduction and voltage stability index improvement are optimized. The power balance and voltage limits are kept as constraints of the problem. The non-sorting pareto-front based multi-objective particle swarm optimization (MOPSO) technique is proposed on standard IEEE 33 radial distribution test system. © JES 2017.